Leisure Studies and Christian Scholarship: Two Solitudes? - Paul Heintzman (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2015)
This paper examines the interrelationships between scholarly Christian writings on leisure and leisure studies literature. As an academic field of study leisure studies is a fairly recent development, however throughout Christian history leisure has been considered by Christians such as Augustine, Aquinas, Luther and Calvin. A number of observations can be made from a review of these two bodies of literature. First, although numerous books have been written in recent decades by Christian scholars on the subject of leisure, very few of these scholars have been leisure studies scholars, and in most cases, these Christian writings have not made reference to some concepts prevalent in leisure studies literature (e.g., leisure as a state of mind, feminist perspectives, serious leisure). Second, with a few exceptions, leisure studies literature rarely references these Christian writings on leisure. Third, leisure studies literature sometimes takes biblical verses out of context and portrays the leisure attitudes and behaviours of some Christian groups such as the Puritans in an overly negative manner. Fourth, the recent interest within the leisure studies field of the relationship between leisure and spirituality offers the possibility of some convergence between the two bodies of literature, although the leisure studies literature tends to favour a more humanistic view of spirituality. In particular, qualitative research studies on leisure and spirituality give a voice to Christian perspectives as expressed through the words of Christian participants.
Keywords: Leisure; spirituality; recreation; religion